Phases and Dynamics of the Social Movement Process in Indonesia: A Case Study on LAPINDO Mudflow Disaster Victims against the Government - Oman Sukmana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study focused on mapping the phases and dynamics of the social movement process of Lapindo mudflow disaster victims in Indonesia. This study was analyzed by using a qualitative. The subject of the study was determined by purposive sampling in which all elements involved in the social movement of mudflow disaster victims. The data were collected by using in-depth interview, observation, FGD, and documentation. The stages of the analysis process involved data reduction, data presentation, and drawing conclusion. The results of the study indicated that the social movements were mapped into three phases: (1) the period of the emergence of the pre-social movement ideas; (2) the period of stabilization and consolidation of the social movements; and (3) the period of the social movement decline. Meanwhile, the dynamics of the social movements of Lapindo mudflow were based on three aspects: (1) political opportunity; (2) mobilizing structure, and (3) cultural framings.